ANALISIS MODEL BUSINESS CANVAS JASA CEK PLAGIASI THE LUCKY OF TURNITIN - Purba, Tiurniari; Nainggolan, Nora Pitri (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2024)
Business Model Canvas (BMC) is a visual chart with nine elements that explain the value proposition of a company or product, infrastructure, customers and finances. The aim of implementing these nine BMC elements is to become a guide in running The Lucky of Turnitin services. BMC determines the best starting from planning The Lucky of Turnitin to realization, as a part of MSMEs managed by students who are still beginners in entrepreneurship. The research method uses descriptive methods, while data analysis uses qualitative analysis. Analysis has been carried out by compiling and verifying BMC. The results of the analysis of The Lucky of Turnitin using the BMC model show that; 1) The Lucky of Turnitin Customer Segments are lecturers and students. 2) Value Propositions using a fast application. 3) The Lucky of Turnitin channels will utilize social media to promote The Lucky of Turnitin through FB posts, official IG, WA stories, and word of mouth promotions. 4) Customer Relationship The Lucky of Turnitin will build relationships with customers by providing testimonials which can be done through assessment testimonials on official IG accounts, WA stories, posts on FB. 5) Revenue Streams for this business come from sales of The Lucky of Turnitin services. 6) Key Resources The Lucky of Turnitin, the main source used by Smartphones, the Internet and Vehicles. 7) Key Activities The Lucky of Turnitin will provide good and quality service quickly. 8) Key Partnership Tawanyesss works with several suppliers that The Lucky of Turnitin needs. 9) Cost Structure (Cost Structure). The costs incurred in this business are divided into several parts, namely Equipment Costs, Raw Material Costs, Packaging Costs and Operational Costs.